Guestbook ghost stories - Shapton, Leanne, author (New York Riverhead Books, 2019)
In a new incarnation of an ancient form--the ghost story--an exploration of the earthly and sublime experience of existence"-- Provided by publisher
Php 500.00
Donated by Gorriceta-Rojo family 10.4.19
Keywords: Short stories, Canadian; Ghost stories, Canadian